INOVASI PENGELOLAAN PEMBELAJARAN BAHASA INGGRIS - Anni Nurhamidah; Rambat Nur Sasongko; Puspa Djuwita (UNIVERSITAS BENGKULU, 2017)
The general purpose of the research is to describe about Innovative Learning Management by the English Teacher at Senior High School 2 South Bengkulu. The research used qualitative descriptive method. The subjects of this research were principals, vice principals, English Teachers and students at the state Senior High School 2 South Bengkulu. The techniques of the collecting data were observation, interview, and documentation study. The general results of the study show that the Innovative Learning Management by the English Teacher at Senior High School 2 South Bengkulu was suitable with the curriculum. The specific results were: 1) Planning was planned successfully; 2) organization was good; 3) Implementation was done perfectly; 4) Evaluation was done continually; 5) The problems in the innovation of English Teaching-Learning Management at Public Senior High School 2 South Bengkulu were about students’ motivation and the facilities at the school.